Bhakti as environmental ethic: assessing the religious Vedic tradition of bhakti-yoga as a potential environmental ethic - Wolfenden, Jurgen Vaugn (Stellenbosch : Stellenbosch University, 2023)
Thesis (MPhil)--Stellenbosch University, 2023.